PENGEMBANGAN EKOSISTEM BISNIS PARIWISATA TERPADU BERBASISKAN STRATEGI 5 JALUR - Edhie Baskoro Yudhoyono (Badan Penelitian dan Pengembangan Provinsi Sumatera Utara, 2021)
Tourism activity is a strategic sector which is expected to contribute significantly to the country's economy. Tourism will contribute maximally to the country's economy, if it is developed in a planned and integrated manner, and collaboration between all stakeholders is required. The purpose of this study is to describe the development of an integrated tourism business ecosystem based on a 5-path strategy. This writing is the result of thinking based on literature studies from various sources, including the results of empirical studies from several previous studies. The 5 (five) track strategy is the development of 4 (four) track strategy consisting of pro growth, pro job, pro poor, and pro-environment which are the thoughts and policies of President SBY during his leadership period plus the 5th track strategy is pro technology. This strategy is applied in the development of an integrated tourism ecosystem in order to increase demand for goods and services in the tourism sector and other sectors that have an impact on increasing economic growth, absorption of labor and reducing poverty in tourism locations by using ICTs in improving tourism performance and encouraging more development environmentally friendly. The tourism business ecosystem must be well understood in order to allocate resources right on target by selecting priorities that will be developed first in tourism. Tourism will contribute maximally to the country's economy, if it is developed in a planned and integrated manner, and collaboration between all stakeholders is required. Integrated tourism must optimize local resources, activities, products, production and service industries, and participatory local communities as an effort to integrate the development and management of tourist attractions, tourism facilities and other economic facilities in one area as a tourism destination.